An exploration of the academic literature about open government - Ibarra Caicedo, Diana Patricia (SATHIRI, 2020)
This article offers a review of the literature published on open government, a concept that encompasses strategies for government transparency, as well as permanent spaces for citizen collaboration and participation. It offers a view of the conception and subsequent adoption of the term, both by the academic community and in the public debate, as well as its dividing line with other similar concepts such as “electronic government”. It seeks to offer an overview of the increase, over the last decade, of the amount of academic information available as a reflection of the penetration and adoption of the idea of open government. The article begins with a theoretical review of the concepts, principles, strategies and trends of open government, continuing with systematic searches whose information is tabulated and included in the text. Finally, some conclusions are offered.
Keywords: open government; transparency; collaboration; participation